Karakteristik Ekstrak Daun Bidara (Ziziphus mauritiana L.) terhadap Variasi Daya Microwave dan Lama Ekstraksi - Purnami, Ni Gusti Ayu Kade Sintya Ari; Wartini, Ni Made; Gunam, Ida Bagus Wayan (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Bidara leave (Ziziphus mauritiana L.) are plants that contain bioactive compound cuch as saponins that have the potential as antioxidants. The saponin content fuctions as a natural surfactant that has the potential to be applied in the soap, cosmetics, and pharmaceutical industries. This study aims to determine the effect of microwave power and extraction time on the characteristics of bidara leaf extract and to determine the best microwave power and extraction time to produce bidara leaf extract using the Microwave Assisted Extraction method. The experimental design used was a factorial Randomized Block Design with 2 factors, namely microwave power consisting of 3 levels, namely 180, 300, and 450 watts and ectraction time also consisting of 3 levels, namely 5, 9, and 13 minutes. Data analysis was carried out using (Analysis of Variance) and if the treatment affect the observed variables, it was continued with (Duncan’s Multiple Range Test). The results showed that microwave power and extraction time significantly affected the yield, saponin content of the crude extract, foam height, and antioxidant capacity. The interaction between treatments significantly affected the saponin content of the crude extract. However, the ineraction did not significantly affect the yield, foam height, and antioxidant capacity. The best treatment to produce bidara leaf extract as a source of saponins was obtained based on the effectiveness index test with a microwave power of 450 watts and an extraction time of 13 minutes with the characteristics of a yield value of 31.38 ± 1.24%, a saponin content of the crude extract of 60.80 ± 0.57%, a foam height of 9.17 ± 0.71 mm, and an antioxidant capacity of 3.54 ± 0.23 mg GAEAC/g.